A, The To What Extent has the Local Government Optimized Open Government Data through the “Satu Data” Platform in Pekanbaru City? - Dini Permata; M. Rafi (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2026)
The implementation of Open Government Data (OGD) constitutes an integral part of the public governance reform agenda that emphasizes transparency, accountability, and public participation. In this context, the Government of Pekanbaru City has adopted the One Data policy as a platform for the integration and dissemination of data across local government agencies. However, the extent to which OGD principles have been optimized through this platform in local governance practice remains an issue that requires further examination. Therefore, this article aims to analyze the level of OGD optimization. This study employs a descriptive qualitative method through a literature review by examining policy documents, scholarly publications, and official information from the local government. The findings indicate that the Government of Pekanbaru City has established a foundational framework for OGD through regulatory arrangements, the development of a data portal, and efforts to strengthen human resource capacity. Nevertheless, the optimization of OGD has not yet been fully achieved, as evidenced by limited data interoperability, inconsistent data updates, and low levels of public data utilization. The scientific novelty of this article lies in its empirical analysis, which not only assesses the existence and availability of data but also examines the degree of operationalization of OGD elements in supporting transparency, inter-agency coordination, and the utilization of data in the formulation and evaluation of public policies in Pekanbaru City. Based on these findings, it can be concluded that OGD optimization in Pekanbaru City remains at the stage of institutional strengthening and has not yet reached an optimal level, thereby requiring further strategic efforts to enhance the quality and value of public data.